Signs and symptoms of oral and skin manifestations in children with COVID-19: narrative review (Research, Society and Development, 2021)
The coronavirus 2019 disease pandemic is caused by the severe acute respiratory syndrome coronavirus 2. The most common clinical symptoms are fever, headache, sore throat, dyspnea, dry cough, abdominal pain, vomiting, and diarrhea. The relationship between COVID-19 and infection in pediatric patients has some peculiarities. In babies under one year of age, with COVID-19 it is more common to have feeding difficulties and fever, whereas in children up to nine years old, dry cough and fever are more recurrent. People who are aged between 10 and 19 years, add muscle pain, shortness of breath, diarrhea, lack of smell and taste, in addition to runny nose. However, in most children, COVID-19 may be asymptomatic, and thus there is less knowledge of the possible manifestations in childhood. The objective of this study was to carry out a narrative review of the literature on oral and cutaneous manifestations in children affected by COVID-19, in order to identify specific lesions that could facilitate diagnosis and treatment. Methodology: The bibliographic search strategy was performed in the PubMed databases of works published from January 2020 to August 2, 2021 using search terms related to oral and dermatological manifestations presented in children with COVID-19. Results: 135 results were found, of which, after the inclusion criteria, 35 were selected for the initial study and after the elimination of the exclusion criteria, there were 26 articles for the study of this work. After reading the texts, the oral and dermatological manifestations observed in children with COVID-19 were: erythema, chilblain-like lesions, strawberry-like tongue, vesicular and maculopapular eruptions, skin irritation, urticaria, conjunctivitis and multisystem inflammatory syndrome. Conclusion: The signs and symptoms in children with COVID-19 have some peculiarities when compared to adults. This study has some limitations, mainly because it addresses a recent subject and a population restricted to pediatrics. However, it is important for the professional to have this knowledge and to explore clinically and exhaustively any manifestation that the child may present during the pandemic.